Password-based authenticated key establishment for wireless group communications in an ad-hoc mode. (6th November 2008) - Wu, Shuhua; Zhu, Yuefei
With the advancement of wireless technology and the increasing demand for mobile devices, secure and efficient password authenticated key establishment technologies are needed for various kinds of secure communications among wireless devices. In this paper, we propose a simple and elegant password-based authenticated key establishment protocol for wireless group communications in an ad-hoc mode. The protocol allows users to securely join and leave the wireless group at time, accommodates either a single-shared password or pairwise-shared passwords among the group members or at least with a central server. Our protocol is rather efficient, especially when compared to the previous solutions in the literature. Furthermore, we can prove its security under the assumptions that the hash function closely behaves like a random oracle and that the computational Diffie-Hellman problem is difficult and that the underlying encryptions are indistinguishable under chosen-plain-text attack.